IMPLEMENTASI PROGRAM DESA TAHAN BENCANA DALAM MENINGKATKAN KESIAPAN MASYARAKAT DI DESA CIPAYUNG DATAR KECAMATAN MEGAMENDUNG KABUPATEN BOGOR - Wira Muharromah; Adi Subiyanto Subiyanto; Fauzi Bahar Bahar; Pujo Widodo; wilopo wilopo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Formation Village Tough Disaster in Cipayung Datar Village, Megamendung District Bogor Not yet Once evaluated to date so this study aims to evaluate implementation program Village Tough Disaster the. Study This using a qualitative method with a descriptive design. The aim of this research is to explain the implementation of the disaster resilient village program in the village Cipayung. Theory Which used in This research is the theory of policy implementation by George Edward III who identify a number of factor supporters implementation policy, that is communication, source Power, trend or behavior, And structure bureaucracy. Data collection techniques through observation and studies documentation with research subjects in Cipayung village. Data analysis techniques used include data reduction, data presentation, and withdrawal conclusion. Results study show that village disaster resilience in Cipayung villages is at on levels primary And level preparedness public in Village Cipayung Datar is at a level that is still not optimal. Implementation program experience obstacle from source Power man And funding.